2019
DOI: 10.21203/rs.2.16131/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why under five children are stunted in Pakistan? Multilevel analysis of Punjab Multiple Indicator Cluster Survey (MICS-2014)

Abstract: Background : Pakistan is facing an acute problem of child under-nutrition as about 38 percent of

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
0
8
0
3
Order By: Relevance
“…This result is consistent with findings from similar studies conducted in Egypt, Bangladesh, Ghana, India, Pakistan, and Eswatini [ 3 , 12 14 , 19 , 21 , 33 ]. The association could be linked to inadequate complementary feeding practices and exposure to infections as the children get older in resource-poor settings [ 13 , 37 , 38 ]. In comparison to female children, male children were shorter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with findings from similar studies conducted in Egypt, Bangladesh, Ghana, India, Pakistan, and Eswatini [ 3 , 12 14 , 19 , 21 , 33 ]. The association could be linked to inadequate complementary feeding practices and exposure to infections as the children get older in resource-poor settings [ 13 , 37 , 38 ]. In comparison to female children, male children were shorter.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the findings from other studies [ 3 , 12 14 , 19 , 21 , 24 , 33 , 38 ], we found that maternal education (secondary/higher secondary) was positively associated with HAZ of children. In studies from various settings, educated mothers were found to have a better knowledge about nutrition, childcare, child feeding, hygiene, risk associated with poor diet, and healthcare practices in comparison to non-educated counterparts, which could have positively influenced growth and development of children [ 3 , 13 , 14 , 18 , 19 , 41 , 42 ]. Similar to Fenske et al [ 33 ], Mahmood et al [ 13 ] and Simelane et al [ 14 ], we found a positive association between improved toilet facility and HAZ of children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported that inadequate nutrition is the major risk factor for the child malnutrition [9]- [11]. Studies have found that there are multiple factors associated with child undernutrition such as low birth-weight, mother's education, mother's body mass index (BMI), sex of the child, birth order, poor exclusive breast feeding, poor sanitation practices, poverty, dietary diversity, and social inequalities [9], [10], [12]- [16]. Some studies have shown that an individual and community level factors are responsible for the childhood undernutrition [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, due to its long-term and negative repercussions, undernutrition is one of the most urgent issues of our day [8]. A number of studies reported that inadequate nutrition is the major risk factor for the child malnutrition [9]- [11]. Studies have found that there are multiple factors associated with child undernutrition such as low birth-weight, mother's education, mother's body mass index (BMI), sex of the child, birth order, poor exclusive breast feeding, poor sanitation practices, poverty, dietary diversity, and social inequalities [9], [10], [12]- [16].…”
Section: Introductionmentioning
confidence: 99%